2001
DOI: 10.1053/joca.2000.0423
|View full text |Cite
|
Sign up to set email alerts
|

The transglutaminase, Factor XIIIA, is present in articular chondrocytes

Abstract: FXIIIA is present in articular chondrocytes. FXIIIA levels correlate with TGase activity in chondrocytes. The presence of two forms of TGase in articular chondrocytes suggest an important function for this enzyme family in articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…Chondrocytes have the capacity to release FXIIIA Nurminskaya et al, 2002;Rosenthal et al, 2001). In this study, we identified novel functional implications of upregulation of FXIIIA expression and release in both the growth plate chondrocyte hypertrophic differentiation program and in OA cartilage chondrocytes Nurminskaya and Linsenmayer, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…Chondrocytes have the capacity to release FXIIIA Nurminskaya et al, 2002;Rosenthal et al, 2001). In this study, we identified novel functional implications of upregulation of FXIIIA expression and release in both the growth plate chondrocyte hypertrophic differentiation program and in OA cartilage chondrocytes Nurminskaya and Linsenmayer, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…To date, the transglutaminase family consists of 9 different TG genes (2). Tissue transglutaminase (TG2, type II) is one of the best-characterized, skeletal tissue-related TGs (3,4) and may be involved in the initiation of mineralization and play an important role in ossification (5,6). …”
Section: Introductionmentioning
confidence: 99%
“…Transglutaminase activates latent TGF-β to increase chondrocyte ePPi production. Two dominant forms of transglutaminase have been identified in articular cartilage-type II transglutaminase and factor XIIIA [24]. Interleukin-1-beta (as well as tumor necrosis factor-alpha, donors of nitric oxide, and the potent oxidant peroxynitrite) induces increased chondrocyte transglutaminase activity [20].…”
Section: Calcification Mechanism: Role Of Extracellular Inorganic Pyrmentioning
confidence: 99%